2011
DOI: 10.4103/0378-6323.84065
|View full text |Cite
|
Sign up to set email alerts
|

White piedra of scalp hair by Trichosporon inkin

Abstract: White piedra is a rare fungal infection of hair and is reported to be all the more rare on scalp. Trichosporon inkin is usually associated with white piedra of pubic hair. We report a case of white piedra of scalp hair caused by T. inkin. This is the first case reported from India and the fifth case reported worldwide. A 50-year-old Muslim female presented with white knots over scalp hair. Diagnosis of Trichosporon was made by examining KOH mounts of epilated hair and Lactophenol Cotton Blue preparations of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
2
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…In the systematic review by Ramírez-Soto et al [6], it was found that T. inkin is the main etiologic agent of white piedra on the scalp in patients over 15 years of age, which could explain this distribution of cases between age groups. The patient in the present case, aged 38, and a 50-year-old Indian patient [15], were the ones with the highest age in the cases analyzed, ages that are not so usual in cases of white piedra.…”
Section: Discussionmentioning
confidence: 43%
See 2 more Smart Citations
“…In the systematic review by Ramírez-Soto et al [6], it was found that T. inkin is the main etiologic agent of white piedra on the scalp in patients over 15 years of age, which could explain this distribution of cases between age groups. The patient in the present case, aged 38, and a 50-year-old Indian patient [15], were the ones with the highest age in the cases analyzed, ages that are not so usual in cases of white piedra.…”
Section: Discussionmentioning
confidence: 43%
“…N.I., not informed. [15], were the ones with the highest age in the cases analyzed, ages that are not so usual in cases of white piedra.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Trichosporon species has been identified as the causative agent in all reported cases from India; however, all cases were from tropical regions (South India and Chandigarh). [78910] Ours is the first case from a temperate region. A definite relationship between the yeast causing white piedra and geographic location needs to be ascertained in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Both black-and-white piedra occur predominantly in humid tropical and semi-tropical areas (Africa, South America, and Asia). [34567] However, white piedra has been reported from temperate climatic areas like Europe, USA and Japan as well. Common sources of infection in both types are stagnant water and soil.…”
Section: Discussionmentioning
confidence: 99%